Some bounds for the minimum edge dominating energy of graphs - Movahedi, Fateme; Mohamad Hadi Akhbari; Roslan Hasni; Nabeel Ezulddin Arif; Sumarni Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2025)
The minimum edge dominating energy, denoted by EEF (G), of a graph G is the sum of the absolute values of eigenvalues of the minimum edge dominating matrix with respect to a minimum edge dominating set F of the graph G. In this study, some bounds for the minimum edge dominating energy are obtained.